2014
DOI: 10.1108/jpbm-12-2013-0466
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of media types and congruence in positioning of service brands

Abstract: Purpose – The purpose of this paper is to undertake a comparative examination of the media types used in projecting positioning strategies of service brands, and to establish whether there is evidence of congruence/fit between managerial decisions, adopted communications and target audience perceptions of positioning strategies of the brands. The relative congruence among intended, conveyed and perceived brand positions is an important research task. Also, how to ensure such synergy and minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Therefore, the task of evaluating the effectiveness of this positioning exercise is of paramount significance. It is also supported by Seggev (1982), Rossiter and Percy (1997), Alden, Steenkamp, and Batra (1999), Blankson (2004), and Blankson, Kalafatis, Coffie, and Tsogas (2014), who further indicate that since the ultimate objective of product/service/brand (offering) advertising emanates from positioning activities, the main concern of marketers and researchers must be the assessment of the degree to which desired positioning has been accomplished. Accordingly, an attempt is made to evaluate the offering's positions in the marketplace in the case of four popular Indian car brands.…”
Section: Introduction and Background Of The Studymentioning
confidence: 93%
“…Therefore, the task of evaluating the effectiveness of this positioning exercise is of paramount significance. It is also supported by Seggev (1982), Rossiter and Percy (1997), Alden, Steenkamp, and Batra (1999), Blankson (2004), and Blankson, Kalafatis, Coffie, and Tsogas (2014), who further indicate that since the ultimate objective of product/service/brand (offering) advertising emanates from positioning activities, the main concern of marketers and researchers must be the assessment of the degree to which desired positioning has been accomplished. Accordingly, an attempt is made to evaluate the offering's positions in the marketplace in the case of four popular Indian car brands.…”
Section: Introduction and Background Of The Studymentioning
confidence: 93%
“…Previous research has identified some components to measure brand positioning (Blankson et al, 2014;Fuchs and Diamantopoulos, 2010;Malik et al, 2016). It has also shown that BCP is related to such factors as country-of-origin (Adina et al, 2015), market segmentation (Green, 2015), consumer preferences and perceptions (Lee and Liao, 2009) and product attributes (Gwin and Gwin, 2003).…”
Section: Brand Competitive Positioning's Components Antecedents and Consequentsmentioning
confidence: 99%
“…The aim of this step was to produce a pool of items to tap the domains of the construct supported by theoretical conceptualizations and exploratory research. To obtain an initial list of items, the existing literature on BCP (Adina et al, 2015;Blankson and Strutton, 2011;Blankson et al, 2014;Chen et al, 2017;Fuchs and Diamantopoulos, 2010;Green, 2015;Iyer et al, 2019;Magnusson et al, 2019;Malik et al, 2016;Wason and Charlton, 2015) has been evaluated and the main indicators and factors were extracted for BCP, including distinctiveness/uniqueness, desirability/favorability, credibility, value for money and top of the mind awareness. We also classified the effective factors on BCP (Table 1).…”
Section: Step 1: Exploring Brand Competitive Positioning Components and Influencing Factorsqualitative Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian tentang Luxury brand telah dilakukan oleh para Ilmuwan dalam beberapa Kategori misalnya : Pertama, Luxury brand di relasikan dengan Aspek Psikologis Konsumen , Nilai, dan kejiwaaan Konsumen antara lain (Amaral et al, 2013;Blankson, Kalafatis, Coffie, & Tsogas, 2014;Brannen & Frisby, 2017;Jeong & Jang, 2018;Khare, Mishra, & Parveen, 2012;Liu, Li, Mizerski, & Soh, 2012;Rajagopal, 2018;Rajat Roy andFazlul K. Rabbanee2013), 2010;Salem & Salem, 2018) Khare et.al (2012), Blankson et.al ( 2014 ) . Kedua, Lux brand dihubungkan dengan Lintas Budaya ( cross-culture ), budaya konsumen dilakukan oleh beberapa peneliti antara lain : (Farah & Fawaz, 2016;Perez, Castaño, & Quintanilla, 2010;Potavanich, 2015;Wu, Luo, Schroeder, & Borgerson, 2017).…”
unclassified